Determination Of Apparent Diffusion Coefficient Of Blood At Its Various Ages Using The Technique Of Diffusion Mri - Taib, Hartini Mohd (2010)
The aim of this study is to develop ADC calibration plot in diffusion MRI and to examine the signal intensity trend of MR-weighted T1-, T2-, proton density and Fluid Attenuated Inversion Recovery images as a function of time ranged from 1 hour to 60 days. Fresh human blood samples were drawn from four volunteers and divided into 3 different categories namely, blood mixed with Citrate-Phosphate-Dextrose-Adenine (CPDA), blood mixed with thromboplastin and untreated blood as control. A set of T1WI, T2WI, PD, FLAIR and DWI were acquired using 1.0 Tesla MRI system (GE Signa Horizon LX) at Hospital Universiti Sains Malaysia. Measurements of the signal intensity for T1WI, T2WI, PD and FLAIR images were performed using GE ADW 2.0 Software. The reconstruction of the ADC maps and measurement of the ADC values for DWI were carried out using GE ADW 2.0 (Functool) Software. The study demonstrates that there is a significant trend displayed by all types of images. The trend was obviously exhibited in T1WI, PD and DWI. Generally the curves obtained can be divided into three parts.